Pain and Addiction in Specialty and Primary Care: The Bookends of a Crisis. Issue 2 (June 2018) - Schottenfeld, Joseph R.; Waldman, Seth A.; Gluck, Abbe R.; Tobin, Daniel G.
Specialists and primary care physicians play an integral role in treating the twin epidemics of pain and addiction. But inadequate access to specialists causes much of the treatment burden to fall on primary physicians. This article chronicles the differences between treatment contexts for both pain and addiction — in the specialty and primary care contexts — and derives a series of reforms that would empower primary care physicians and better leverage specialists.